Implementation of Institutional Da'wah Values in the Political Communication Process at the Bandung City General Election Commission - Firdaus, Dadan; Hikmat, Mahi Mamat; Mardiansyah, Yadi (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
This research finds different points of view in the political communication process carried out by the Bandung City KPU during the selection process for Bandung mayoral candidates. This research was conducted to analyze the good values within the KPU institution from an institutional da'wah perspective. By using a subjective interpretive approach, qualitative methods, and descriptive case study research, this research describes the problems that occurred at the 2018 Bandung Mayor candidate stage as material for improvement for the 2024 Bandung Mayor election as well as mapping political communication da'wah that can be developed by the City General Election Commission Bandung in the framework of finding solutions to problems at the nomination stage. The results of the research concluded that the nomination stage in the 2018 Bandung Mayor election had five issues, so genuine efforts and policies were needed from the Bandung City General Election Commission to improve the nomination stage for the 2024 Bandung Mayor election. One of the efforts that can be made to deal with problems at the nomination stage is developing two political communication da'wah activities, namely the application of the shura method exemplified by Rasulullah SAW in internal political communication, both horizontally and vertically organizational and external political communication between the Bandung City General Election Commission and the citizens of Bandung, especially the prospective candidates for Mayor of Bandung in various forms of da'wah political communication, both face to face and media political communication to realize honest and fair elections.